PENGARUH TAI CHI EXERCISE TERHADAP PENINGKATAN FUNGSI PARU PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA BUDI MULIA 3 CILANDAK, JAKARTA SELATAN TAHUN 2023 - Ali, Mohammad; Sariana, Erna; Salsabila, Ananda Vio (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Background: All humans will experience an aging process in all part of their body organs and systems, including aging in the respiratory system that causes circulation of the air into the lungs . Functionally, the lungs will decrease oxygen capacity in the elderly. Oxygen or O2 is a basic human needed of the body and it is also needed to continue the metabolism of cells in the body, carrying out life and operated of various tissues and organs of the body. Purpose: This study aims to determine the effect of Tai Chi Exercise on improving lung function in the elderly. Method: This study used a purposive sampling quantitative experimental research with a quasi-experimental pretest-posttest two group control design. Determination of the sample using the Lameshow formula and obtained 2 treatment groups with a total of 18 respondents selected based on inclusion criteria. Pulmonary function was using a spirometry as instrument with the results of FEV1/FVC obtained at the beginning and ending of the intervention in 3 times a week for 4 weeks study. Result: The final results of the study found that there was a difference effect between the group with the Tai Chi Exercise intervention (mean : 37,5 + 8,1) and the group that did not receive the Tai Chi Exercise intervention (mean 11,4 + 7,8). Sugestion: Furthermore, the researchers suggest that research should be carried out with a longer period of time for better results.